Comparative analysis of endoscopic-assisted burr hole craniostomy and two burr hole craniostomy in the treatment of septated chronic subdural hematoma - An, Yaqing; Cheng, Hongbo; Wang, Xiaoliang; Men, Yijiao; Yu, Jiegang; Zhang, Gengshen; Li, Jiaming; Zuo, Tao; Yu, Baohai; Wu, Jianliang; Wu, Yang (Frontiers in Neurology, 2025)
ObjectiveTo conduct a retrospective comparative analysis of endoscopic-assisted burr hole craniostomy (EBHC) vs. two burr hole craniostomy (TBHC) in the management of septated chronic subdural hematoma (sCSDH).MethodsThis study employed a retrospective cohort design, encompassing 87 patients diagnosed with sCSDH who were admitted for EBHC or TBHC between January 2018 and December 2023. Among these patients, 48 underwent EBHC, while 39 received TBHC. The primary outcome measure was the recurrence rate within 6 months following surgery. Secondary outcomes included clinical outcomes at discharge and 6 months, duration of hospitalization, and duration of drainage tube placement.ResultsThe recurrence rates were comparable between EBHC and TBHC groups (12.5% vs. 10.3%, p = 0.742). However, the mean operative time was significantly longer for the EBHC group, averaging 103.56 ± 20.93 min, in contrast to the TBHC group, which averaged 50.77 ± 12.40 min (p < 0.001). Additionally, the mean placement time for the drainage tube was significantly shorter in the EBHC group (18.66 ± 5.89 h) compared to the TBHC group (55.87 ± 23.03 h, p < 0.001). Furthermore, the mean length of hospital stay was notably reduced for the EBHC group (6.02 ± 1.68 days) compared to the TBHC group (4.66 ± 1.79 days, p < 0.001). There were no significant differences in mortality rates, complication rates, MRS scores, GCS scores, or the presence of gross focal neurological deficits postoperatively between the groups.ConclusionTBHC is an effective intervention for sCSDH, offering a less invasive alternative with shorter operative duration and comparable recurrence rates to EBHC. Nonetheless, the efficacy of this approach requires further validation through large, multicenter studies.